PENGARUH PEMASARAN DIGITAL, INOVASI PRODUK DAN KUALITAS PRODUK TERHADAP PENINGKATAN PENJUALAN PRODUK UMKM DI MASA PANDEMI COVID-19 (STUDI KASUS PADA PELAKU UMKM DI KABUPATEN LAMPUNG BARAT) - Arianzah, Ahmad Taufik; Indriani, Wiewiek; Listyaningsih, Erna; Mufahamah, Euis; Harun, Harmani (Jurnal Jejama Manajemen Malahayati, 2023)
The influence of micro, small and medium enterprises on the economy of West Lampung Regency is very large but there are still problems that still need to be resolved. This quantitative   research   was   conducted   to   determine   the   effect   of digital marketing, product innovation   and   product   quality   partially   and simultaneously on increasing   product   sales   for   micro,   small   and   medium enterprises. The data collection technique in this study was through observation, distributing questionnaires to 40 respondents who are also small and mediumsized business actors    assisted    by    the     Small     and     Medium     Enterprises     Cooperatives, Industry and Trade Office of West Lampung Regency using google forms   and literature studies. From the results of data analysis that has been carried out, it is obtained that digital marketing   has   an   effect   on   increasing   sales,   product innovation has an effect on the variable of increasing sales, product quality has an effect on increasing sales and   digital   marketing   variables,   product   innovation and product quality will have a simultaneous effect on the variable of increasing sales.